COVID Chronicles : A Comics Anthology - Zhu, Annie; Zen; You Wu, Richard; Williams, Ian; Wall, Shelley; Tornado, Tamara; Tobocman, Seth; Thummler, Brenna; Summers, Chris; Stossel, Sage; Stephens, Jay; Steinberg, Emily; et al. (Book collections on Project MUSE., 2021)
In 2020, the COVID-19 pandemic brought the world to its knees. When we weren't sheltering in place, we were advised to wear masks, wash our hands, and practice social distancing. We watched in horror as medical personnel worked around the clock to care for the sick and dying. Businesses were shuttered, travel stopped, workers were furloughed, and markets dropped. And people continued to die. Amid all this uncertainty, writers and artists from around the world continued to create comics, commenting directly on how individuals, societies, governments, and markets reacted to the worldwide crisis. COVID Chronicles: A Comics Anthology collects more than sixty such short comics from a diverse set of creators, including indie powerhouses, mainstream artists, Ignatz and Eisner Award winners, and media cartoonists. In narrative styles ranging from realistic to fantastic, they tell stories about adjusting to working from home, homeschooling their kids, missing birthdays and weddings, and being afraid just to leave the house. They probe the failures of government leaders and the social safety net. They dig into the racial bias and systemic inequities that this pandemic helped bring to light. We see what it's like to get the virus and live to tell about it, or to stand by helplessly as a loved one passes. At times heartbreaking and at others hopeful and humorous, these comics express the anger, anxiety, fear, and bewilderment we feel in the era of COVID-19. Above all, they highlight the power of art and community to help us make sense of a world in crisis, reminding us that we are truly all in this together. The comics in this collection have been generously donated by their creators. A portion of the the proceeds from the sale of this volume are being donated by the publisher to the Book Industry Charitable Foundation (Binc) in support of comics shops, bookstores, and their employees who have been adversely affected by the pandemic.